2021
DOI: 10.1038/s41598-021-85709-1
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific antigen-adjuvant conjugation using cell-free protein synthesis enhances antigen presentation and CD8+ T-cell response

Abstract: Antigen-adjuvant conjugation is known to enhance antigen-specific T-cell production in vaccine models, but scalable methods are required to generate site-specific conjugation for clinical translation of this technique. We report the use of the cell-free protein synthesis (CFPS) platform as a rapid method to produce large quantities (> 100 mg/L) of a model antigen, ovalbumin (OVA), with site-specific incorporation of p-azidomethyl-l-phenylalanine (pAMF) at two solvent-exposed sites away from immunodominant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…We hypothesized that DC activation by free OVA is overshadowed by the potent adjuvant. 31–33 Previous studies and our results have shown that free OVA antigen without adjuvant has poor DC activation efficacy. 34…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…We hypothesized that DC activation by free OVA is overshadowed by the potent adjuvant. 31–33 Previous studies and our results have shown that free OVA antigen without adjuvant has poor DC activation efficacy. 34…”
Section: Resultsmentioning
confidence: 64%
“…We hypothesized that DC activation by free OVA is overshadowed by the potent adjuvant. [31][32][33] Previous studies and our results have shown that free OVA antigen without adjuvant has poor DC activation efficacy. 34 Activated BMDCs could secrete proinflammatory cytokines that recruit and activate T cells, instigating adaptive immune responses.…”
Section: Biomaterials Science Papermentioning
confidence: 67%
“…Having confirmed the efficient lymph node drainage of CpG loaded onto the nanovaccine, we further analyzed the endocytic activity of DCs in different forms of CpG. DC2.4 is a mouse bone marrow dendritic cell line established with C57BL/6 mouse bone marrow cells transfected by the V-myc and V-raf genes and used to simulate the function of APC in several studies [ 30 , 38 ]. By stimulating DC2.4s with CpG Cy5 , NP-OPS+CpG Cy5 , or NP-OPS-CpG Cy5 , the amount of CpG phagocytosed by DC2.4s was analyzed by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…However, this compatibility method requires a large amount of CpG, which increases the cost and potential safety risks. Considering that CpG needs to enter antigen-presenting cells to perform its biological function, researchers also tried to improve the utilization of CpG by coupling it with antigens [ 30 , 31 ]. At present, many CpG and antigen connectors, such as NHS-PEG n -maleimide (SMCC) and the His-hydrophobic-His (HUH) superfamily of endonucleases, have been explored [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%